Key concepts in mental health - Pilgrim, David 1950- (SAGE key concepts., 2023)
This book includes "68 entries covering the breadth of past and contemporary understandings of mental health." It is an "introduction and reference for all professionals who have a stake in other people's mental health." -- from back cover.